2012
DOI: 10.5935/1678-9741.20120061
|View full text |Cite
|
Sign up to set email alerts
|

Associated factors with survivals in patients undergoing orthotopic heart transplant using retrograde blood microcardioplegia

Abstract: Fatores associados à sobrevida em pacientes submetidos a transplante cardíaco utilizando microcardioplegia sanguínea retrógrada Associated factors with survivals in patients undergoing orthotopic heart transplant using retrograde blood microcardioplegia Abstract Background: Several techniques and cardioplegic solutions have been used for heart preservation during transplant procedures. Unfortunately, there is a lack of ideal method for myocardial preservation in the clinical practice. The use of retrograde c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…However, for human tissue donations, donors that had evolved into CRA are accepted. The number of corneal tissue donations has increased from donors who were given the diagnosis of BD and had evolved to CRA [ 11 , 12 ] . In the analysis of the profile of BVCH donors, it was observed that there is less family refusal in situations in which the potential donor was in CRA.…”
Section: Discussionmentioning
confidence: 99%
“…However, for human tissue donations, donors that had evolved into CRA are accepted. The number of corneal tissue donations has increased from donors who were given the diagnosis of BD and had evolved to CRA [ 11 , 12 ] . In the analysis of the profile of BVCH donors, it was observed that there is less family refusal in situations in which the potential donor was in CRA.…”
Section: Discussionmentioning
confidence: 99%
“…There are a great range of myocardial protection solutions on the market and modes of infusion in heart transplant [ 10 - 12 ] . However, there is controversy on the superiority of one solution over the others.…”
Section: Discussionmentioning
confidence: 99%